2016
DOI: 10.18632/oncotarget.11627
|View full text |Cite
|
Sign up to set email alerts
|

PARP3 controls TGFβ and ROS driven epithelial-to-mesenchymal transition and stemness by stimulating a TG2-Snail-E-cadherin axis

Abstract: Several members of the Poly(ADP-ribose) polymerase (PARP) family are essential regulators of genome integrity, actively prospected as drug targets for cancer therapy. Among them, PARP3 is well characterized for its functions in double-strand break repair and mitotis. Here we report that PARP3 also plays an integral role in TGFβ and reactive oxygen species (ROS) dependent epithelial-to-mesenchymal transition (EMT) and stem-like cell properties in human mammary epithelial and breast cancer cells. PARP3 expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 55 publications
(79 reference statements)
5
54
0
3
Order By: Relevance
“…As CSCs seem able to preferentially resist drugs-induced DNA damage [22]. We continued exploring whether NRP-1 is involved in doxorubicin sensitivity via conferring CSCs formation in breast cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…As CSCs seem able to preferentially resist drugs-induced DNA damage [22]. We continued exploring whether NRP-1 is involved in doxorubicin sensitivity via conferring CSCs formation in breast cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…It is well established that ROS promotes EMT in mammary epithelial or breast cancer cells through diverse mechanisms [69, 70]. It is suggested that the activation of EGFR is involved in alcohol-promoted EMT [49] and alcohol may activate EGFR through intracellular ROS accumulation [66].…”
Section: Cellular and Molecular Mechanisms Underlying Alcohol-indumentioning
confidence: 99%
“…FAM63B, LOC401464 and PARP3 autoantibodies could not be confirmed in the validation assays (Figure ), and hence, their relevance as immune targets in narcolepsy could not be verified. PARP3 is an enzyme with regulatory functions of processes including DNA damage responses and has been reported as a negative regulator of immunoglobulin class switch recombination . Protein expression is found in all major organs, including the brain .…”
Section: Discussionmentioning
confidence: 99%